2016
DOI: 10.1002/cphc.201600050
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Orientational Order Parameters Determined from Two‐dimensional X‐ray Diffraction Patterns: A Simulation Study

Abstract: The orientational order parameter S2 is one of the most important quantities to describe the degree of long-range orientational ordering of liquid crystals. There are several approaches to experimentally measure this order parameter of liquid crystalline phases but every method includes substantial simplifications and assumptions. We present a simulation-based approach to elucidate the reliability of the method of Davidson, Petermann and Levelut to measure S2 via 2D X-ray experiments. We have found that this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…It is interesting to note that a study of the reliability of order parameters determined from X-ray scattering patterns, carried out using the LN model, concluded that the approach underestimates the true values of hP 2 i by ca. 0.03-0.06 [38,39]; the results shown in Figure 7 suggest that this underestimation may at least partially be attributed to the error in Equation (4) in the LN approach. An equivalent comparison of hP 4 i values determined from the same scattering patterns of 5CB, 6CB, 7CB and 8CB was also carried out, as shown in Figure 8.…”
Section: Comparison Of Ln Kratky Lm and Baseline Correction Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is interesting to note that a study of the reliability of order parameters determined from X-ray scattering patterns, carried out using the LN model, concluded that the approach underestimates the true values of hP 2 i by ca. 0.03-0.06 [38,39]; the results shown in Figure 7 suggest that this underestimation may at least partially be attributed to the error in Equation (4) in the LN approach. An equivalent comparison of hP 4 i values determined from the same scattering patterns of 5CB, 6CB, 7CB and 8CB was also carried out, as shown in Figure 8.…”
Section: Comparison Of Ln Kratky Lm and Baseline Correction Methodsmentioning
confidence: 95%
“…This expression readily enables the order parameters, hP L i, to be determined from the integrated intensity of the wide-angle X-ray peaks, the method for which is described fully in the literature [23]. As a result of the increasing ease of carrying out X-ray scattering studies of liquid crystal samples, this method has been used widely in the field of liquid crystal studies to interpret experimental data [ 14,15,17,[24][25][26][27][28][29][30][31][32][33][34][35], as well as forming the basis for a number of computational and theoretical studies [36][37][38][39]. Outside the field of liquid crystals, it was noted over a decade ago by Burger and Ruland that there had been an error in the derivation of Equation (4) [40], and that the correct formula had in fact been derived much earlier by Kratky [41].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] One of the most important methods to investigate the order of a liquid crystalline phase is X-ray diffraction. [4][5][6][7][8][9][10][11][12][13][14][15] The diffraction pattern of an aligned SmA phase exhibits two sets of intensity maxima. The diffuse and broad wide angle maxima correspond to the mean short distance of molecular centers.…”
Section: Introductionmentioning
confidence: 99%
“…While the validity of methods to extract information about the orientational order of a liquid crystal has been discussed the validity of methods that extract information about the translational order is still an open question. In general, the X‐ray intensity Iboldq is proportional to the structure factor Sboldq and the form factor F2boldq in the sample volume (IboldqF2boldq·Sboldq ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation